"Why do I always see double?" A misdiagnosed case of ocular myasthenia gravis for 10 years. (2nd May 2014) - Mohamed Yousuf, Uduman Ali; Yashodhara, B M; Thanigasalam, Thevi; Ting, Heng Siang
Abstract : A 58-year-old man presented with diplopia and partial ptosis for 10 years. It was non-progressive in nature, despite inadequate medical attention the patient received from non-specialists/general practitioners. He did not have fatigability or diurnal variation in weakness and was clinically stable without exacerbations of disease for a decade. He did not have features of Graves's disease, oculopharyngeal dystrophy, cranial nerve paralysis, polymyositis and stroke. The possibility of an atypical presentation of myasthenia gravis (MG) was considered and the patient was evaluated. Ice pack test was negative, Cogan's lid twitch (CLT) test was positive and high titres of acetylcholine receptor antibodies (AChR Ab) suggestive of MG were found. He was treated accordingly with a very good response.